Grammar and Translation Methods in Arabic Language Learning: Theory and Practice - Afriati, Intan; Ratmansyah, Zuhir; Fadhil, Ardiman; Lesmana, Yudistira Iriandi (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to examine the effectiveness of grammar-translation methods in teaching Arabic through a literature study approach. This method is a classic approach that has been widely used in learning foreign languages, including Arabic, especially in traditional Islamic educational environments such as Islamic boarding schools and madrasas. The main focus of this method is on mastery of grammatical structures and the ability to translate texts, rather than on active communication skills. In the modern era that demands communicative and contextual language skills, questions arise about the relevance and effectiveness of this method in meeting the needs of contemporary learning. This study uses a descriptive qualitative approach with a literature research design. Data was obtained from the analysis of various literature such as books, scientific journals, dissertations, curricula, and relevant previous research results. The data analysis technique is carried out in a descriptive-analytical manner, with steps of data reduction, data presentation, and conclusion drawn. The results of the study show that grammar and translation methods have advantages in terms of understanding language structure and access to classical texts, but are limited in the development of speaking and listening skills. Therefore, the effectiveness of this method is highly dependent on the context and objectives of the learning. In certain situations, this method can still be used strategically if combined with other, more communicative approaches. This study recommends a balanced methodological integration between structural and functional approaches so that Arabic language learning is more adaptive to the needs of the times.